Environmental and material criticality assessment of hydrogen production via anion exchange membrane electrolysis - Schropp, Elke; Campos-Carriedo, Felipe; Iribarren, Diego; Naumann, Gabriel; Bernäcker, Christian; Gaderer, Matthias; Dufour, Javier (Applied energy, 2024)
The need to drastically reduce greenhouse gas emissions is driving the development of existing and new technologies to produce and use hydrogen. Anion exchange membrane electrolysis is one of these rapidly developing technologies and presents promising characteristics for efficient hydrogen production. However, the environmental performance and the material criticality of anion exchange membrane electrolysis must be assessed. In this work, prospective life cycle assessment and criticality assessment are applied, first, to identify environmental and material criticality hotspots within the production of anion exchange membrane electrolysis units and, second, to benchmark hydrogen production against proton exchange membrane electrolysis. From an environmental point of view, the catalyst spraying process heavily dominates the ozone depletion impact category, while the production of the membrane represents a hotspot in terms of the photochemical ozone formation potential. For the other categories, the environmental impacts are distributed across different components. The comparison of hydrogen production via anion exchange membrane electrolysis and proton exchange membrane electrolysis shows that both technologies involve a similar life-cycle environmental profile due to similar efficiencies and the leading role of electricity generation for the operation of electrolysis. Despite the fact that for proton exchange membrane electrolysis much less material is required due to a higher lifetime, anion exchange membrane electrolysis shows significantly lower raw material criticality since it does not rely on platinum-group metals. Overall, a promising environmental and material criticality performance of anion exchange membrane electrolysis for hydrogen production is concluded, subject to the expected technical progress for this technology. •Life Cycle Assessment of an Anion Exchange Membrane Electrolysis (AEMEL) unit.•Criticality assessment of the AEMEL technology as a complement to its environmental evaluation.•Benchmarking of AEMEL hydrogen against that from Proton Exchange Membrane Electrolysis (PEMEL).•Similar environmental performance of hydrogen produced through AEMEL and PEMEL.•Overall criticality score of AEMEL is negligible compared to the PEMEL alternative.